2016
DOI: 10.1007/s11427-016-5105-7
|View full text |Cite
|
Sign up to set email alerts
|

Osteoimmunology: memorandum for rheumatologists

Abstract: Rapid progress has been made in exploring the connections between the skeletal system and the immune system over the past decade. Bone tissue forms developmental niches for hematopoietic stem cells, and activated immune cells are involved in bone metabolism regulation and are potent mediators of osteoporosis and bone erosion under pathological conditions. The interdisciplinary field of osteoimmunology has emerged to pool the knowledge of the interdependence of these two systems, including the shared ligands an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 187 publications
0
9
0
1
Order By: Relevance
“…Recent findings led to a research focus on different proinflammatory factors, as well as their role in osteoclastogenesis (Pietschmann et al, 2016;Michalski and McCauley, 2017). Estrogen withdrawal will lead to an increase in inflammatory cytokines, and these mediators majorly contribute to excessive osteoclastogenesis and bone resorption in menopause-associated bone loss (Zhao et al, 2016;Pietschmann et al, 2016;Michalski and McCauley, 2017). As PUN has considerable anti-inflammatory effects (Wang et al, 2019), we wondered whether PUN can suppress inflammation in osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent findings led to a research focus on different proinflammatory factors, as well as their role in osteoclastogenesis (Pietschmann et al, 2016;Michalski and McCauley, 2017). Estrogen withdrawal will lead to an increase in inflammatory cytokines, and these mediators majorly contribute to excessive osteoclastogenesis and bone resorption in menopause-associated bone loss (Zhao et al, 2016;Pietschmann et al, 2016;Michalski and McCauley, 2017). As PUN has considerable anti-inflammatory effects (Wang et al, 2019), we wondered whether PUN can suppress inflammation in osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that PUN directly inhibited osteoclastogenesis in vitro. Growing evidence indicates that inflammation plays an important role during osteoclast formation and bone resorption (Zhao et al, 2016). Therefore, we next examined whether PUN has a direct inhibitory effect on inflammation.…”
Section: Pun Inhibited the Macrophage Proinflammatory Phenotype And Pmentioning
confidence: 99%
See 1 more Smart Citation
“…However, osteoimmunology demonstrated that the immune system and immune factors may be involved in the development of osteoporosis and play important regulatory roles [ 2 , 3 ]. The microenvironment created by bone cells provides conditions for development of the immune system, which regulates bone metabolism via B cells, T cells, dendritic cells, and many cytokines [ 2 5 ]. Abnormal activation of the immune system alters the balance between osteoblasts and osteoclasts, which results in an imbalance in bone remodeling and causes osteoporosis [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development and response of immune cells associate to bone remodeling; on the other hand, activated immune cells are involved in bone metabolism regulation, and mediate osteoporosis and bone erosion under pathological conditions such as rheumatoid arthritis (RA), spondyloarthropathy (SPA), osteoporosis (OP), and periodontal disease (PD). In this issue, Zhao et al presented current understanding of osteoimmunology and emphasized on the RANK/RANKL/OPG signaling in bone remodeling and immune responses (Zhao et al, 2016). Recent research progress in the interactions between T cells, B cells, DCs and bone cells, in the role of several kinds of cytokines including M-CSF, TNF-α, IL-1, IFN-γ, IL-4, IL-10, IL-6, TGF-β, OPN and complement system in bone homeostasis were also summarized in this review, particularly their pathogenesis in major diseases.…”
mentioning
confidence: 99%